Ocelová konstrukce mostu středního rozpětí - Dovičic, Boris (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práca sa zaoberá návrhom nosnej oceľobetónovej konštrukcie cestného mostu. Konštrukcia premosťuje železničnú trať a vodný tok v intraviláne okresného mesta Blansko. Osová vzdialenosť uloženia mostu je 99,8 m. Konštrukcia mostu je riešená v troch variantoch s výberom najvhodnejšieho variantu. Pri návrhu a výpočtoch boli dodržané platné české technické normy a technické predpisy pre navrhovanie mostov.

The diploma thesis deals with the design of the load-bearing composite steel and concrete structure of the road bridge. The structure span a railway line and a watercourse in the urban area of the district town of Blansko. The centre to centre spacing of the bridge supports is 99.8 m. The construction of the bridge is solved in three variants with the selection of the most suitable variant. Valid Czech technical standards and technical regulations for designing bridges were observed during the design and calculations.
Mid-Span Bridge Steel Structure
Keywords: Spriahnutý oceľobetónový most; cestný most; dolná mostovka; Langerov trám; rombická sústava; krivopásova pravouhlá sústava; priehrada; composite steel and concrete bridge; road bridge; lower bridge deck; Langer beam; rhombic system; curvilinear rectangular system; truss